Diagnóstico y tratamiento de la etapa aguda del accidente cerebrovascular isquémico: Guía de práctica clínica del Seguro Social del Perú (EsSalud) - Sequeiros-Chirinos , Joel Mario (2020)
Objective: to provide evidence based clinical recommendations for the diagnosis and therapy of the acute stage of ischemic cerebrovascular accident in EsSalud. Materials and methods: a group for producing the guideline was conveyed, including specialized physicians and methodologists. The group prepared 8 clinical questions to be answered by the guideline. Systematic searches of previous reviews were performed, and – when it was deemed necessary – primary studies in Medline and the Cochrane Controlled Registry of Trials for 2018 were reviewed. Evidence was selected aiming to respond each one of the proposed clinical questions. Certainty of the evidence was determined using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodic work sessions, the group used GRADE methodology for reviewing the evidence and generated recommendations, good clinical practice items, and designed flow charts for both diagnosis and therapy. Finally, the guide was approved with the decree N° 128-IETSI-ESSALUD-2019. Results: this clinical practice guideline focused in 8 clinical questions, which were divided into four topics: screening, diagnosis, therapy, support and rehabilitation. On the basis of these questions, 28 recommendations were formulated (8 strong and 20 conditional), 38 items for good clinical practice, 1 implementation note, and 2 flow charts. Conclusion: this paper summarizes both evidence based methodology and conclusions from a new clinical practice guide for diagnosis and therapy of the acute stage of a cerebrovascular accident in EsSalud.